The Deleuze dictionary - Parr, Adrian (Edinburgh : Edinburgh University Press, 2005)
Dedicated to the work of Gilles Deleuze, this work provides an in-depth introduction to one of the most influential figures in continental philosophy.
Includes bibliographical references.
Keywords: Deleuze, Gilles, -- 1925-1995 -- Dictionaries